Semisynthesis and biological activity of stemofoline alkaloids - Morwenna C. Baird (2018)
The semisynthesis of the Stemona alkaloids (3′R)-stemofolenol (1), (3′S)-stemofolenol (2), methylstemofoline (3), and (3′S)- hydroxystemofoline (5) and the unnatural analogues (11E)-methylstemofoline (15) and 3′R-hydroxystemofoline (11) has been achieved starting from (11Z)-1′,2′-didehydrostemofoline (4). This synthesis allowed, for the first time, access to diastereomerically enriched samples of 1 and 2 and the assignment of their absolute configurations at C-3′. These compounds were obtained in sufficient quantities to allow for their biological testing. In a quantitative assay as AChE inhibitors, (11Z)-1′,2′- didehydrostemofoline (4) and (3′S)-hydroxystemofoline (5) were found to be the most active. © 2009 American Chemical Society and American Society of Pharmacognosy.